A proposta da ética das virtudes de MacIntyre : interfaces com a política contemporânea - Rosa, Aléssio da (Universidade do Vale do Rio dos Sinos, 2018)
The advent of the Enlightenment during the eighteenth century in Europe undermined the foundations of morality, hitherto supported by philosophies of classical and medieval heritage. Alasdair MacIntyre, in 1981, with the publication of the work After Virtue, undertook a philosophical project based on the rehabilitation of a form of rational research in which the practices that constituted the moral narratives and traditions, based and updated from the seminal concept of virtues Aristotle-Tomasic basis. MacIntyre, by interconnecting concepts - vulnerability, dependence and rational autonomy - establishes the perception of virtues as a communitarian and cooperative trait, without reducing them to the quality of individual or social character or merely emotional traits. The present work aims at assessing the plausibility of the virtue ethics, recontextualized by MacIntyre, as a reference paradigm for contemporary politics. We seek to argue about the viability of the ethical model of virtues and its implications for today's society, characterized as pluralistic and multicultural. We argue in favor of an ethic that can be an effective alternative in overcoming contemporary hedonist / consumerist individualism, seeking a possible policy of virtues according to MacIntyre's conception. A new policy, which can be an alternative to the dichotomous and obliterated vision of a life decanted in projects committed solely for profit, to the detriment of the well-being of the community, in harmony with nature and other living beings. For this purpose, we present the main bases of the ethics of the virtues thought and updated by MacIntyre, their plausibility, as well as the main objections and questions of opponents and critics of this ethical model.
Keywords: MacIntyre; Ética das Virtudes; Política; Dependência compartilhada; MacIntyre; Ethics of Virtues; Policy; Shared dependency; ACCNPQ::Ciências Humanas::Filosofia